PENGARUH PERBESARAN LUAS ELEKTRODA TERHADAP PROBABILITAS TEGANGAN TEMBUS PADA DIELEKTRIK MINYAK MENGGUNAKAN SUMBER TEGANGAN TINGGI DC - Astari, Bela Natasya; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
The electrode is an electrical conductor that is used to determine a breakdown voltage and functions as a tip medium where the positive and negative sides are opposite. The shapes of electrodes are very diverse, one of which is rod electrodes. This research will describe the effect of increasing the electrode area on the probability of breakdown voltage in oil dielectrics using high DC voltage. The research method used is to collect data through testing breakdown voltage, leakage current and oil conductivity at the High Voltage Laboratory, Department of Electrical Engineering, Faculty of Engineering, Brawijaya University and carrying out electric field simulations for each variation of electrode area magnification with FEMM 4.2 software. The electrode variations used in testing breakdown voltage and leakage current are A, 2A, 3A, 4A, and 5A. Breakdown voltage testing was carried out with the same distance between electrodes, namely 2 mm, on an oil dielectric using Shell Diala B oil. The results obtained from this research were the influence of increasing the electrode area on the probability of breakdown voltage and leakage current level. Where the greater the area magnification value, the smaller the breakdown voltage value and the greater the leakage current level. Apart from that, the five variations of electrode area magnification have the same homogeneity factor where the electric field distribution is even. Keywords: Electrodes, Enlargement, Probability, Shell Diala B Oil